Heat flow characteristics and thermal resistance model for soil-rock mixtures during freezing-thawing processes: Damping properties - Jianguo Lu; Yindong Wang; Wansheng Pei; Xusheng Wan; Liling Tan; Fei Deng (Geoderma, 2023)
As a special heterogeneous geological material, soil-rock mixtures are widely distributed in nature and used in civil engineering. Heat flow is one of the most significant factors affecting the development of water balance and redistribution, ground temperature evolution, and heat transport processes in cold regions. This study explores the heat flow characteristics and generalized thermal resistance model for soil-rock mixtures during freezing-thawing processes. A series of freezing-thawing experiments for soil-rock mixtures with different rock contents (i.e., 10%, 25%, and 40%) were conducted. The effects of rock content and water–ice phase transition on heat flux during the freezing-thawing processes were analyzed, and the damping properties of heat flow for soil-rock mixtures during freeze–thaw cycles were found and illustrated. Subsequently, a generalized thermal resistance model for soil-rock mixtures was proposed and discussed. The results show that the freezing-thawing processes and rock content significantly influence the heat flux and soil temperature of the soil-rock mixtures. Regardless of rock content, the sums of heat flux in freezing and thawing stages all firstly decreased, and then gradually tends to be stable with freeze–thaw cycles. Besides, the reduction of volumetric unfrozen water content increases with the freeze–thaw cycles, and the amplitude of unfrozen water reduction for sample with high rock content is larger than that with low rock content. Additionally, owing to the effect of the latent heat released by water/ice phase transition and thermal sensitive property of rock, the variation of heat flow for soil-rock mixtures presents damping property in the stages without completely freezing, and the variation of heat flow exhibits reversed damping property in the post-freezing stages due to the denser structure and ice crystal growth. Furthermore, based on the thermal resistance in series, characteristics of water–ice phase transition, and thermal sensitive property of rocks, a new generalized thermal resistance model of soil-rock mixtures during freezing-thawing processes is proposed.